Compact square spiral printed antenna. Issue 3 (1st January 2014) - Wei, Heng; Lin, Min; Xiang, Yang
Abstract : A novel compact printed antenna with a spiral winding and a loop feed is proposed. After optimising the design parameters, the prototype of the antenna with a small electrical size of 0.043 λc × 0.043 λc × 0.001 λc is fabricated. It is shown that a central frequency as low as 425.9 MHz can be achieved without any additional matching networks, and a good omnidirectional radiation pattern similar to the dipole antenna is obtained.